Sodium Metabisulfite Mediated Synthesis of Bis(pyrazolo[1,5-a] pyrimidin-3-yl)methanes from Pyrazolo[1,5-a]pyrimidines with Dimethyl Sulfoxide as a C1 Synthon - Pattanayak, Paramita; Satyanarayana, Appanapalli N. V.; Saha, Samiran; Keerthana, Hariharasubramanian Sai; Naresh, Ainala; Girase, Yogesh K.; Chatterjee, Tanmay (Synlett, 2024)
We report an unprecedented synthesis of bis(pyrazolo[1,5-a]pyrimidin-3-yl)methanes, a new class of di(hetaryl)methanes, from pyrazolo[1,5-a]pyrimidines by using DMSO as a C1 synthon (methylene source). The transformation is mediated by sodium metabisulfite (Na2S2O5), which plays a crucial role in the presence of acetic acid as a promoter. A wide variety of bis(pyrazolo[1,5-a]pyrimidin-3-yl)methanes were synthesized in moderate to good yields of up to 90%. Mechanistic studies suggested that the reaction follows an ionic pathway, probably involving a methyl(methylene)sulfonium ion as an active electrophilic species formed in situ by the reaction of DMSO with Na2S2O5.
Keywords: sodium metabisulfite; pyrazolopyrimidines; bispyrazolopyrimidinylmethanes; C1 synthons; DMSO; metal-free reaction